Does this case hold the answer to one of the worse types of pain in medicine—that of loin pain haematuria syndrome (LPHS). (26th April 2015) - Russell, Alan; Chatterjee, Suman; Seed, Michael
Abstract : A patient with loin pain haematuria syndrome suffering chronic throbbing pulsing pain overlaid with prolonged periods of incapacitating colic and overnight vomiting was presented 10 months following diagnosis. Ultrasound was normal. No renal or ureteral stones, or filling defects were seen on CT. At cytoscopy, bladder and urethra were normal, and bloody urine effluxed from the left ureteric orifice. The ureters were normal at diagnosis, and developed new abutting non-penetrating calcifications by 8 months. Pain episodes of complete incapacitating intensity of 2–4 h duration were reduced to 10 min with 5 mg crushed tadalafil administered at onset. If tadalafil was delayed to after onset, the original course of agony resulted. Daily tadalafil reduced loin pain intensity, but not the exacerbations. Tadalafil efficacy may indicate that the pain exacerbations are due to spasm of ureter smooth muscle. 5 mg tadalafil taken at onset alleviated severe loin pain exacerbations in this case of loin pain haematuria syndrome.